The strategic framework of tuberculosis control and prevention in the elderly: a scoping review towards End TB targets - Jun Li; Pui-Hong Chung; Cyrus L. K. Leung; Nobuyuki Nishikiori; Emily Y. Y. Chan; Eng-Kiong Yeoh (BMC, 2017)
Abstract With the rapid pace of population ageing, tuberculosis (TB) in the elderly increasingly becomes a public health challenge. Despite the increasing burden and high risks for TB in the elderly, targeted strategy has not been well understood and evaluated. We undertook a scoping review to identify current TB strategies, research and policy gaps in the elderly and summarized the results within a strategic framework towards End TB targets. Databases of Embase, MEDLINE, Global health and EBM reviews were searched for original studies, review articles, and policy papers published in English between January 1990 and December 2015. Articles examining TB strategy, program, guideline or intervention in the elderly from public health perspective were included. Nineteen articles met the inclusion criteria. Most of them were qualitative studies, issued in high- and middle-income countries and after 2000. To break the chain of TB transmission and reactivation in the elderly, infection control, interventions of avoiding delay in diagnosis and containment are essential for preventing transmission, especially in elderly institutions and aged immigrants; screening of latent TB infection and preventive therapy had effective impacts on reducing the risk of reactivation and should be used less reluctantly in older people; optimizing early case-finding with a high index of suspicion, systematic screening for prioritized high-risk groups, initial empirical and adequate follow-up treatment with close monitoring and evaluation, as well as enhanced programmatic management are fundamental pillars for active TB elimination. Evaluation of TB epidemiology, risk factors, impacts and cost-effectiveness of interventions, adopting accurate and rapid diagnostic tools, shorter and less toxic preventive therapy, are critical issues for developing strategy in the elderly towards End TB targets. TB control strategies in the elderly were comprehensively mapped in a causal link pathway. The framework and principals identified in this study will help to evaluate and improve current program, develop targeted strategy, as well as raise more discussions on the research priority settings and policy transitions. Given the scarceness of policy and evaluated interventions, as well as the unawareness of shifting TB epidemiology and strategy especially in developing countries, the increasing need of a ready TB program for the elderly warrants further research.